Spatial inequality in Bangladesh: A geospatial analysis - Abdullah Ar Reyad; Mohammad Sofi Ullah Ullah (International Journal of Basic and Applied Science, 2022)
Spatial inequality of development is an important issue in Bangladesh. In this study a set of sectors-education, infrastructure, health, and economy-and sectoral components/indicators were selected aiming at investigating the spatial inequality scenario of Bangladesh. All components/indicators of each sector were weighted overlaid using ArcGIS tool. Finally, the overall spatial inequality of development was generated overlaying all the sectoral inequality maps. The spatial inequalities were revealed categorically from the highest overlaid cell value as the most lagged area to the lowest value as the most advance area. A serious centralized character towards the capital Dhaka was identified almost in all the sectors in spatial inequality maps of Bangladesh. The overall spatial inequality map identified a total of 16 districts in the comparatively ‘lagged area’ category; and 44 districts in the category of the ‘moderate area’. Only one district (the capital Dhaka) was identified in the category of ‘most advance area’, while three districts (Chittagong, Gazipur, Narayanganj) found in the ‘advance area’ category. Most of the lagged districts were identified in the north-west and north-east parts of Bangladesh. Besides, the districts of Chittagong Hill Tracts (Bandarban, Khagrachari, Rangamati) were also found most lagged..